Islamic Mindfulness-Based Play Activities: Enhancing Child Mental Health in the Post-Pandemic Era - Hayati, Miratul; Nuraida; Salsa Lutfiah Zahra (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
This research focuses on developing Islamic mindfulness-based play activities to mitigate child mental health issues in the post-pandemic context. The study was conducted in Jakarta-Depok kindergartens using a modified Research and development (R&D) approach tailored for educational settings, as per Borg and Gall. The primary aim was to create and evaluate educational tools to foster Islamic mindfulness among young learners. The research involved identifying children's learning challenges post-pandemic and developing and refining educational games and teaching methods. Data collection encompassed observational studies, educator feedback, and direct interaction with children using the developed tools. The analysis evaluated these tools' usability, engagement level, and educational impact. The results highlighted the development of a physical model comprising a 14-chapter guidebook for tea. Still, it is a procedural model that condenses the original ten stages into seven. Essential components include yoga based on prayer movements, activities for enhancing food relationships, self-body awareness exercises, sensory training, gratitude journal writing, and positive affirmations based on Asmaul Husna. Evaluations by material and learning design experts and one-to-one teacher tests affirmed the model's quality. A field trial with 20 children showed enjoyment and preference for gratitude journal writing. Conclusively, the research effectively developed a model for Islamic mindfulness-based play activities, demonstrating the potential to enhance children's mental health post-pandemic. However, limitations such as geographic confinement and individual response variability suggest the need for broader application and further research to assess long-term impacts. This study contributes significantly to educational and psychological interventions, offering a culturally sensitive, holistic child development approach integrating mental health, spirituality, and education.